Hubungan Pendidikan, Pengetahuan dan Masa Kerja dengan Tingkat Kepatuhan Perawat Dalam Penggunaan APD di RS Harum Sisma Medika Tahun 2019 - Restu Iriani (Jurnal Persada Husada Indonesia, 2019)
Hospital is one of the working environments that can threathen the safety and health of health workers, one of them is a nurse. The high number of occupational accidents in nurses is caused nurses disobedience to use of personal protective equipment. The several factors are education, working of periods, and knowledge level of nurses. The purpose of this studies was to determine the correlation of education, working periods, knowledge level with nurse compliance level the use of PPE in Harum Sisma Medika in 2019. This studies was quantitative descriptive with cross sectional approach with sample of 50 nurses in adult inpatients care. The sampling technique uses purposive sampling. The data analysis using chi square test. The result shows that there was no correlation between education with nurse compliance level the use of personal protective equipment (p value=0,365), there was a correlation between working periods with nurse compliance level the use of PPE (p value=0,017, OR=5,688), and there was a correlation between knowledge level with nurse compliance level the use of personal protective equipment (p value= 0,000, OR= 14,583). The recommendation for hospital will always provide training to nurses related to the use of PPE in a prevent to reduce workplace accidents.